Notes on Stuart Jewellery (Proceedings of the Society of Antiquaries of Scotland, 1923)
The jewellery of the Stuart period is of special interest, in particular the exquisite little rings, brooches, and clasps which were worn by the followers and adherents of the Stuart and Jacobite causes. The memorial jewellery, dating from the death of Charles I is often of fine and rare design and workmanship, and the backs of the items are beautifully enamelled in black and white and occasionally in colour. The fronts were mostly formed of a piece of rock-crystal cut in the shape of a rose diamond, and in special cases of a diamond itself covering sometimes a miniature of the king or his initials worked in gold wire surmounted by a crown\r and supported by cherubs. A range of rings, necklaces, earrings, neckslides and pendants are described.